Salted Fish Consumption Factors on the Incidence of Nasopharyngeal Cancer: A Systematic Review - Syafira, Seftiani; Siregar, Salwa Febriana Ekasari; Saputra, Diki; Febriansyah, Rafa Ilham; Ariyanto, Januar (Universitas Mandala Waluya, 2025)
Nasopharyngeal cancer (NPC) is a squamous cell cancer that originates from the epithelial lining of the nasopharynx. The issue of salted fish consumption is a concern because the salt preservation process can produce carcinogenic nitrosamine compounds. The nitrosamine content is formed from the reaction between nitrite, nitrate, and secondary amines, which has the potential to cause cell changes to become malignant if consumed in the long term, especially from an early age. This study aimed to systematically review the consumption pattern of salted fish based on age, frequency of consumption, and its potential risk of NPC and to identify gaps in the results of previous studies. The method used was a systematic review by searching the literature on online databases such as Scopus, PubMed, ScienceDirect, and Garuda. A total of 126 articles were obtained, and 11 articles met the criteria. The results of the analysis showed that there are differences in salted fish consumption patterns based on age and frequency that may increase the risk of NPC, especially in individuals who started consuming in childhood and high amounts. This study highlights the need for further research that considers genetic aspects, types of salted fish, and processing methods in different regions to clarify the causal relationship.